Iliopsoas abscess: clinical presentation, management, and outcome - Benkhadoura, Mohamed O.; El-Mogassabi, Abdulhafid H.; Mansor, Salah M.; Abuzaid, Issa A.; Manita, Muftah A.; Etabbal, Abdalla M.; Elgazwi, Khaled K.; Elshaikhy, Akrem I. (International Surgery Journal, 2018)
Background: The aim of this study was to review our experience with iliopsoas abscesses (IPAs) and evaluate the various drainage procedures. Methods: All consecutive patients with an IPA admitted to three university hospitals between September 2008 and June 2017 were retrospectively included. Results: Of the 26 patients, 17 (65.4%) were male and nine (34.6%) were female, with an average age of 30.7 (17-58) years. Fifteen (57.7%) cases had primary IPAs and Staphylococcus spp. was the most common isolate. Eleven (42.3%) cases had secondary IPAs, and spinal tuberculosis was the most common underlying condition. Lower-back or flank pain was the most common presentation (69.2%). Computed tomography (CT) scans confirmed all clinical diagnoses. All patients were managed via drainage and antibiotic therapy; seven (26.9%) were subjected to open surgical drainage and 19 (73.1%) received percutaneous drainage (PCD) under ultrasound (US) guidance. The average hospital stay was 9.5 days (range 5-18 days). The hospital stay was significantly shorter in patients treated via PCD compared to those who received open drainage: 8.5 days (range 5-14 days) vs. 12.1 days (range 6-18 days), respectively (p = 0.031). The overall recurrence rate was 11.5% (3/26). Recurrence developed in three patients treated via US-guided PCD and all were successfully treated via a second round of PCD. No mortality was recorded. Conclusions: US-guided PCD combined with appropriate antibiotic therapy is safe and effective with shorter hospital stay when used to treat IPAs. Open surgical drainage may be warranted if the IPA is multiloculated or if there is an underlying pathology.